The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11064-008-9897-0
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of d-serine Might Induce GABAergic Neuronal Degeneration in the Cerebral Cortex and Hippocampus in the Mouse Pilocarpine Model of Epilepsy

Abstract: Epilepsy is a serious neurological disorder with neuronal loss and spontaneous recurrent seizures, but the neurochemical basis remains largely unclear. We hypothesize that D-serine, a newly identified endogenous co-agonist of N-methyl-D-aspartate (NMDA) receptor, may trigger excitotoxicity and neuronal damage in epileptogenesis. By using a mouse pilocarpine model, immunohistochemistry, Fluoro-Jade staining and double-labeling, the present study revealed up-regulation of D-serine expression in a proportion (41%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In addition, d-serine, a recently identified endogenous co-agonist of NMDA receptor , may trigger excitotoxicity and neuronal damage in epileptogenesis. By using the pilocarpine model in mice, it has been shown up-regulation of d-serine expression in a large proportion of neurons in cortex and hippocampus but not in other brain regions (Liu et al, 2009). This study revealed that most of d-serine-positive neurons were GABAergic (98%), underwent degenerating death (93%), and were accompanied enhancing phosphorylation of NMDA receptor subunit 1.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, d-serine, a recently identified endogenous co-agonist of NMDA receptor , may trigger excitotoxicity and neuronal damage in epileptogenesis. By using the pilocarpine model in mice, it has been shown up-regulation of d-serine expression in a large proportion of neurons in cortex and hippocampus but not in other brain regions (Liu et al, 2009). This study revealed that most of d-serine-positive neurons were GABAergic (98%), underwent degenerating death (93%), and were accompanied enhancing phosphorylation of NMDA receptor subunit 1.…”
Section: Discussionmentioning
confidence: 76%
“…These findings suggest that d-serine signaling cascades may be involved in the selective death of GABAergic neurons through NMDA receptor over-activation and excitotoxicity following pilocarpine insult. Furthermore, Liu et al (2009) proposed that those events may be involved in early pathogenesis and recurrent seizures associated with chronic epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results indicate that colocalization of D-serine with GABA (as with colocalization of glycine with GABA) is specific to some neuronal populations. In rodents, the presence of D-serine in some GABAergic cells has only recently been reported for the cerebral cortex and hippocampus in a mouse pilocarpine model of epilepsy (Liu et al, 2009). The presence of D-serine in numerous GABAergic cells and, possibly, in some glycinergic cells suggests that many of the D-serinecontaining brain neurons in lamprey are inhibitory cells in which D-serine would contribute putatively to local modulation of neighboring cells and processes.…”
Section: D-serine Immunoreactivity In the Lamprey Brain Is Found In Nmentioning
confidence: 99%
“…Brain levels of D-serine appear to modulate important brain functions, and the control of D-serine level in the brain may be important for neuroprotection against various neurodegenerative diseases (Inoue et al, 2009;Liu et al, 2009). Brain D-serine is synthesized mostly by the enzyme serine racemase, which converts L-serine to D-serine in a highly selective manner (Dunlop and Neidle, 1997;Wolosker et al, 1999;De Miranda et al, 2002), whereas the enzyme D-amino acid oxidase (DAO) is involved in the elimination of free serine (Nagata, 1992).…”
mentioning
confidence: 99%
“…The hippocampus, a part of limbic system in the brain, is involved in memory formation and affective state. In addition, this region is associated with some brain diseases such as seizure, ischemia, and Alzheimer's disease (Hwang et al 2009;Liu et al 2009). Recently, this region has received additional attention because neurogenesis occurs in the hippocampal dentate gyrus throughout life (Eriksson et al 1998;Gage et al 1998;McDonald and Wojtowicz 2005).…”
Section: Introductionmentioning
confidence: 99%